UPAYA PENINGKATAN JUMLAH PENERIMAAN DANA DI SMK PELITA NUSANTARA 2 SEMARANG - Luhgiatno . (STIE Pelita Nusantara Semarang, 2006)
In recent of five year there is a sign declining of the total new student in SMK Pelita Nusantara 2 Semarang in other way total need of operational funds in increase. In this research, author decide the situational purpose to increase total income of funds on the school fee from Rp 969.525.000,at education years of 2005/2006 become Rp. 1.100.000.000,ad education years of 2006/2007. To reach this situational purpose, be decide seven fix function of the company, forexample transaction function, take by force of customer function, production function, personal management function, and management accounting function.To measure off the class of already from seven function of this book, author use SWOT analysis to some factors to some factors that involved in the appearance of fix functions at SMK Pelita Nusantara 2 Semarang.The product of factors analysis from unready function are customer factor at the transaction function, product factor to be sale at the take by force of customer function and production function, money factor to market planning function, government factor at research market and marketing function.The recommendations that give in this research are (1) In order to head master recommend with the establishment to talk about the basic of making of master plan that begin from adjustment of the school fees, the entrance fees and the practice fees. (2) Increase new favorite direction (automotive mechanic). (3) Marketing activities that planned and programmed. (4) Be decided computerized of database that integrated, including accounting data that the system was referred to SAK.